THE EFFECT OF STEAM PROJECT-BASED LEARNING BY ENGINEERING DESIGN PROCESS ON PROBLEM-SOLVING ABILITY FOR GRADE 8 STUDENTS: ผลการจัดการเรียนรู้โดยใช้โครงงานสะตีมเป็นฐานด้วยกระบวนการออกแบบเชิงวิศวกรรมที่มีต่อความสามารถในการแก้ปัญหา สำหรับนักเรียนระดับชั้นมัธยมศึกษาปีที่ 2 - Detphiphatworakul, Thitiphat; Kiddee, Krissana; Petsangsri, Sirirat (Journal of Education and Innovation, 2020)
The objectives of this research were 1) to develop a lesson plan of STEAM Project-based Learning by engineering design process to develop on students’ problem-solving ability, 2) to study the effectiveness of a learning process of STEAM Project-based Learning by engineering design, and 3) to compare of problem-solving ability between the students learning with STEAM Project-based Learning by engineering design process and the students learning with normal teaching. This research was an experimental research. The samples of this study were 80 grade 8 students from a secondary school in Bangkok. A total number of 80 students were randomly selected by using cluster random sampling method. They were divided into an experimental group (n = 40) was taught using STEAM Project-based Learning by engineering design process and a control group (n = 40) was taught using normal learning method. The research instruments consisted of 1) the lesson plan of STEAM Project-based Learning by engineering design process, 2) the worksheets (STEAM Project) received validity (IOC) between 0.71-1.00, and 3) problem-solving ability test was valid (IOC) between 0.57-1.00, reliability at 0.90. The statistical methods used in data analysis are Percentage, Mean, Standard Deviation, Inter-rater Reliability (Pearson’s Correlation), and Independent Sample t-test. The results of this research revealed that; 1. The quality of a STEAM Project-based Learning by engineering design process lesson plan from experts in curriculum and teaching received the overall quality at the highest level ( = 4.77, SD = 0.46). 2. The effectiveness of STEAM Project-based Learning by engineering design process learning method according to standard (E1/E2) was equal to 79.53/77.03 complies with the standards that defined not lower than 75/75. 3. The problem-solving ability of the students in STEAM Project-based Learning by engineering design process was significantly higher than the students in normal learning at the level of .05.